2020
DOI: 10.1097/wno.0000000000001000
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Intracranial Hypertension: Glymphedema of the Brain

Abstract: Background : During the last decade, our understanding of cerebrospinal fluid (CSF) physiology has dramatically improved thanks to the discoveries of both the glymphatic system and of lymphatic vessels lining the dura mater in human brains. Evidence acquisition :We detail the recent basic science findings in the field of CSF physiology and connect them with our current understanding of the pathophysiology of idiopathic intracranial hypertension (IIH).Results : Transverse sinus stenoses appear to play a major c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 33 publications
1
22
0
1
Order By: Relevance
“…CSF withdrawal not only lowers CSF pressure, but also promotes the turnover of CSF, and I believe that CSF drainage may favorably affect the fluid dynamics of the glymphatic system, and that this could be an alternative explanation as to why CSF withdrawal may be beneficial in a subgroup of CFS patients [29] . As discussed below, this latter view [29] is now supported by very recent observations confirming that a significant proportion of CFS patients represent a variant of IIH [30] and that IIH may be considered as a manifestation of “glymphedema” of the brain [31] .…”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…CSF withdrawal not only lowers CSF pressure, but also promotes the turnover of CSF, and I believe that CSF drainage may favorably affect the fluid dynamics of the glymphatic system, and that this could be an alternative explanation as to why CSF withdrawal may be beneficial in a subgroup of CFS patients [29] . As discussed below, this latter view [29] is now supported by very recent observations confirming that a significant proportion of CFS patients represent a variant of IIH [30] and that IIH may be considered as a manifestation of “glymphedema” of the brain [31] .…”
Section: Discussionmentioning
confidence: 68%
“…In a very recent state-of-the art review, Nicholson et al [31] detailed the new discoveries of both the glymphatic system and lymphatic vessels lining the dura mater in human brains, and connected them with our current understanding of the pathophysiology of IIH. The authors concluded that IIH can be summarized in the following pathological triad: restriction of the venous CSF outflow pathway, overflow of the compensating lymphatic CSF outflow pathway, and congestion of the glymphatic system.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations